Material world a global family portrait - Menzel, Peter 1948-; Mann, Charles C.; Kennedy, Paul; Eisert, Sandra (San Francisco, CA Sierra Club Books, 1995)
Photographs show the homes and possessions of average families in thirty countries around the world and document each family's lifestyle.
Methodology -- Africa -- Televisions of the world -- Asia -- Latin America -- North America -- Islands -- Meals of the world -- Europe -- Toilets of the world -- Middle East.
Includes bibliographical references (page 250)
Keywords: Material culture -- Cross-cultural studies; Families -- Cross-cultural studies; Economic development -- Cross-cultural studies; Material culture -- Pictorial works .; Families -- Pictorial works